Modulation of lithium ion transport and cycling stability using rigid and flexible urethane moieties on the backbone of polymers - Kargude, Radhakisan; Rajendran, Prakash Babu; Kika, Sharmin Percy; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2025)
Graphite is the anode of choice for lithium-ion batteries. Due to volume change and poor conductivity of inorganic materials, they do not show comparable performance to that of graphite. Conjugated polymers are attractive because of their modularity and ease of synthesis. Herein, we report three polymers based on diketopyrrolopyrrole (DPP) as the anode. In an energy device, stored charges are due to a diffusive and capacitive component. Increasing the capacitive component is a challenge in both organic and inorganic systems. In our polymers, we installed urethane moieties that increase the capacitive component. The excellent Li+ ion transporting urethane moiety is part of the polymer chain. The Li+ ion transport is also impacted by the packing of the polymer chain. Therefore, the DPP units and urethane moieties are connected with either an alkyl chain, phenyl or biphenyl. The polymers with either alkyl or phenyl spacers showed stable cycling stability over 4000 charge-discharge cycles. On the other hand, the specific capacity of the batteries comprising a polymer with biphenyl started decreasing after 500 charge-discharge cycles. This is due to the solubility of the polymer in the battery electrolyte. The polymer with a phenyl spacer showed a higher Li+ ion diffusion coefficient due to the space generated between the polymer chains. The X-ray photoelectron spectroscopy analysis showed that the Li+ ions are bound to carbonyls, indicating the role of urethane in the charge transport. The polymer with an alkyl spacer showed a very high specific capacity of 600 mAh/g (1500th cycle) at a current density of 0.2 A/g, which is much higher than the theoretical capacity of graphite (372 mAh/g). The charge storage in all these polymers is dominated by a capacitive component, with the highest metric of 81% shown by a polymer with an alkyl spacer.
Keywords: Cycling stability; diketopyrrolopyrrole; high capacity; lithium-ion battery; non-conjugatedpolymer; urethane